Internal hydrogen bonding in benzo[a]pyrene diol and diol epoxide metabolites - Capomacchia, Anthony C. (1989)
Fluorescence, excitation, and emission spectra of some benzo[a]pyrene diols and diol epoxides in aqueous and non-aqueous media have been studied and ground- and excited-state dissociation constants have been determined. Spectral shifts due to changes in salvation, Stokes shifts, and pKa and pKa* values are employed to show that the diols and diol epoxides possess an intramolecular hydrogen bond between ortho hydroxy groups when in non-aqueous media. In aqueous media no internal hydrogen bonding occurs either between ortho hydroxy groups or hydroxy and epoxide groups. The latter point is significant with regard to the carcinogenic reactivity of anti- and syn-7,8-dihydroxy 9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene.